Quality of selected groundwater sources in Barangay Kirayan Sur, Miagao, Iloilo - Sy, Maricris R. (2002.)
The study was conducted to assess the physico-chemical and microbiological quality of groundwater sources in Barangay Kirayan Sur, Miagao, Iloilo.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Groundwater; Kirayan Sur, Miagao, Iloilo